2012
DOI: 10.1530/jme-12-0024
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific selection of stable reference genes for real-time PCR normalization in an obese rat model

Abstract: Obesity is a complex pathology with interacting and confounding causes due to the environment, hormonal signaling patterns, and genetic predisposition. At present, the Zucker rat is an eligible genetic model for research on obesity and metabolic syndrome, allowing scrutiny of gene expression profiles. Real-time PCR is the benchmark method for measuring mRNA expressions, but the accuracy and reproducibility of its data greatly depend on appropriate normalization strategies. In the Zucker rat model, no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 35 publications
3
35
0
Order By: Relevance
“…39 In contrast, Cabiati et al identified TFRC as the least stable RG among ten candidates in cardiac and pulmonary tissues of obese and hyperglycemic rats. 40 The contrary results of TFRC gene expression stability depending on which species and tissue was analyzed show the importance of verifying the stability of internal control genes for each experimental setup. We do not recommend using TFRC as a RG for the combined analysis of 2D and 3D cultivated BM-MSCs, as the gene expression was significantly upregulated for BM-MSCs cultivated under 2D conditions.…”
Section: Discussionmentioning
confidence: 99%
“…39 In contrast, Cabiati et al identified TFRC as the least stable RG among ten candidates in cardiac and pulmonary tissues of obese and hyperglycemic rats. 40 The contrary results of TFRC gene expression stability depending on which species and tissue was analyzed show the importance of verifying the stability of internal control genes for each experimental setup. We do not recommend using TFRC as a RG for the combined analysis of 2D and 3D cultivated BM-MSCs, as the gene expression was significantly upregulated for BM-MSCs cultivated under 2D conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted by the acid guanidinium thiocyanate-phenol-chloroform method using an RNeasy Midi kit (Qiagen) following the manufacturer's instructions, as previously described (Cabiati et al, 2012(Cabiati et al, , 2013. The RNA concentration and purity were determined spectrophotometrically (BioPhotometer, Eppendorf, Milano, Italy) measuring spectral absorption at 260 nm.…”
Section: Experimental Animal Modelmentioning
confidence: 99%
“…Real-Time polymerase chain reaction (PCR) reactions were performed in duplicate in the Bio-Rad C1000Ô thermal cycler (CFX-96 Real-Time PCR detection systems; Bio-Rad Laboratories), as previously described (Cabiati et al, 2012(Cabiati et al, , 2013. For monitoring cDNA amplification, a third-generation fluorophore, EvaGreen, was used (SsoFAST EvaGreen Supermix; Bio-Rad Laboratories).…”
Section: Real-time Polymerase Chain Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three housekeeping genes, GAPDH, HPRT1, and bactin, were used as endogenous controls to standardize the amount of cDNA. Thermal cycling conditions were one cycle of 2 minutes at 50 C and one cycle of 10 minutes at 95 C, followed by 40 cycles of amplification for 15 s at 95 C and 1 minute at 60 C. Cycle threshold values were obtained and quantification was performed by the relative expression method using the geometric mean of the housekeeping genes [27]. Negative controls had no reverse transcriptase added.…”
Section: Real-time Pcr For Detection Of Mrna Of Nprs and Natriuretic mentioning
confidence: 99%